From Socialism to Market Economy: The Transition Period - Matejko, Alexander J. (Relations industrielles / Industrial Relations, 1993)
The article reviews the book, "From socialism to market economy: the transition period," edited by William S. Kern.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; economic development

The Three Worlds of Welfare Capitalism - Matejko, Alexander J. (Relations industrielles / Industrial Relations, 1992)
The article reviews the book, "The Three Worlds of Welfare Capitalism," by Gösta Esping-Andersen.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Welfare economics

The Sociology Of Management - Matejko, Alexander J. (Relations industrielles / Industrial Relations, 1991)
The article reviews the book, "The Sociology Of Management," by Mike I. Reed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Management; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Capitalism and Modernity: An Excursus on Marx and Weber - Matejko, Alexander J. (Relations industrielles / Industrial Relations, 1991)
The article reviews the book, "Capitalism And Modernity: An Excursus On Marx And Weber," by Derek Sayer.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Capitalism; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Business And Government In Canada - Matejko, Alexander J. (Relations industrielles / Industrial Relations, 1991)
The article reviews the book, "Business and Government in Canada," by Stephen Brooks and Andrew Stritch.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Business government relations; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Grupa pracownicza jako przedmiot i podmiot motywowania [Polish] [Work Group as an Object and Subject of Stimulation] - Matejko, Alexander J. (Relations industrielles / Industrial Relations, 1990)
The article reviews the book, "Grupa pracownicza jako przedmiot i podmiot motywowania," by Alicja Kozdroj.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

British and Norwegian Offshore Industrial Relations : Pluralism and Neo-Corporatism as Contexts of Strategic Adaptation - Matejko, Alexander J. (Relations industrielles / Industrial Relations, 1990)
This article reviews the book, "British and Norwegian Offshore Industrial Relations : Pluralism and Neo-Corporatism as Contexts of Strategic Adaptation," by Svein S. Andersen.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

A Portrait of Bureaucracy. The Bankruptcy of the Socialist System in Poland - Matejko, Alexander J. (Relations industrielles / Industrial Relations, 1993)
The article reviews the book, "A Portrait of Bureaucracy. The Bankruptcy of the Socialist System in Poland," by Adam Sarapata.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z